Синтез литературы и естественнонаучных методов в творчестве Э. Золя - Терещенко, К.С. (Культура народов Причерноморья, 2013)
Предлагаемая работа посвящена рассмотрению синтетичности в литературе Эмиля Золя. Целью статьи является анализ его произведений, в которых использованы естественнонаучные методы. Автор в процессе творчества превращался в исследователя, объясняя человеческие поступки с научной точки зрения. Он придавал большое значение среде, считая главной задачей писателя изучение взаимного воздействия друг на друга общества и индивидуума. Эмиль Золя утверждал тождество целей искусства и экспериментальной науки. Робота, що пропонується, присвячена розгляду синтетичності у літературі Еміля Золя. Метою статті є аналіз його творів, в яких використані природничонаукові методи. Автор у процесі творчості перетворювався на дослідника та пояснював людські вчинки з наукової точки зору. Він надавав велике значення середовищу, вважав головним завданням письменника вивчення взаємного впливу один на одного суспільства та індивідуума. Еміль Золя затверджував тотожність цілей мистецтва та експериментальної науки. This work is devoted to the synthesity review in the literature by Emile Zola. The aim of the article is the analysis of his selected works in which the methods of natural sciences were used. According to the writer the purpose of literature is to reveal the objective laws determining our life. Within the creative process E. Zola turned into the researcher and explained the human behavior from the scientific point of view. A person itself was considered to be the consequence of the social conditions, physiological nature, heredity, and surroundings. The heroes’ actions, each change in their lives were analyzed in detail and interpreted from the positions of physiology and psychology. The author believed that physiology was the source of all mental reactions. He attached great importance to the environment and considered that the main task of a writer was to study the mutual influence of an individual and society. E. Zola maintained that the aims of art and experimental science were identical.